The Prophet and the Messenger and Their Related Concepts - Mohammed Hikmat Suleiman,; Alaa Jassim Mohammed, (Islamic Sciences Journal, 2025)
ABSTRACT Belief in prophets and messengers (peace be upon them) is one of the pillars of faith. In this research, I have explained the definition of a prophet and a messenger and the difference between them, as well as the evidence for belief in prophets and messengers. I have also clarified the opinion of scholars on this matter, as the opinions of Imams Zamakhshari and Razi (may Allah have mercy on them) on the distinction between prophets and messengers, and the need for humans for the mission of prophets and messengers. I also explain the status of our Prophet Muhammad (peace be upon him) among the prophets